Association of a CAMK2A genetic variant with logical memory performance and hippocampal volume in the elderly - Rhein, Cosima; Mühle, Christiane; Lenz, Bernd; Richter-Schmidinger, Tanja; Kogias, Georgios; Boix, Fernando; Lourdusamy, Anbarasu; Dörfler, Arnd; Peters, Oliver; Ramirez, Alfredo; Jessen, Frank; Maier, Wolfgang; et al. (Brain research bulletin, 2020)
Calcium/Calmodulin-dependent kinase alpha (alpha CaMKII) has been shown to play an essential role in synaptic plasticity and in learning and memory in animal models. However, there is little evidence for an involvement in specific memories in humans. Here we tested the potential involvement of the alpha CaMKII coding gene CAMK2A in verbal logical memory in two Caucasian populations from Germany, in a sample of 209 elderly people with cognitive impairments and a sample of 142 healthy adults. The association of single nucleotide polymorphisms (SNPs) located within the genomic region of CAMK2A with verbal logical memory learning and retrieval from the Wechsler Memory Scale was measured and hippocampal volume was assessed by structural MRI. In the elderly people, we found the minor allele of CAMK2A intronic SNP rs919741 to predict a higher hippocampal volume and better logical memory retrieval. This association was not found in healthy adults. The present study may provide evidence for an association of a genetic variant of the CAMK2A gene specifically with retrieval of logical memory in elderly humans. This effect is possibly mediated by a higher hippocampal volume.
Gesehen am 16.04.2021